A INFLUÊNCIA DAS TEORIAS ECONÔMICAS NA DECISÃO DE TERCEIRIZAR O DESPACHO ADUANEIRO NO SETOR DE COMÉRCIO ATACADISTA NA CIDADE DE SÃO PAULO - Ambrosio, Guilherme Fernando Molina (2014)
The central aim of this work is to present the influence of economic theories in the decision of wholesale firms in to outsource customs clearance in Sao Paulo. For this, the history of outsourcing is displayed briefly, next the surveys and studies on outsourcing and justifications theories that show possible influences on firms decision to outsource customs clearance, such as: Transaction Cost Theory, Agency Theory, Resource-Based View Theory and Core Competence Theory. Addition to contextualize Brazilian foreign trade, considering its history and economic representativeness, will be presented the activities related to customs clearance, which can influence companies to outsource this service in the city of Sao Paulo. After the explanation on the subject, through empirical research making use of questionnaire with closed questions applied to a non-probabilistic sample, it was found a relationship between the theories mentioned above and how they influence the process of companies importing and exporting wholesale to outsource customs clearance. We used the ANOVA test and possible additions to the Dunnett T3 test and Tukey test and it was found that there are difference in responses between respondents who outsource fully, partially or not outsource this activity besides the difference between these levels of outsourcing it was found that all economic theories presented in this work have some influence on outsourcing of customs clearance